INFLAMMATORY REACTION AGINST MYCOPLASMA GALLISEPTICUM INFECTION IN BROILER - & Ali, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was carried out to investigate the Inflammatory reaction in broiler chicken after experimental infection with Mycoplasma gallisepticum(MG) , which were evaluated by using Enzyme Linked Immunosorbent Assay(ELISA) to measure pro inflammatory cytokines and IgG. one hundred day old broiler chicks were randomly divided into five groups 20 birds each group, all groups except group 5 (control) were infected at two weeks old with 0.2ml of 106 cfu/bird of local MG ,groups treated as follows: Group1 : infected Intravenous( I.V) with MG isolate. Group2: : infected Intraocular (I.O) ,Group3: infected Intranasal (I.N),Group4: : infected Intratracheal (I.T) infection, Group5: were not: infected with MG isolate. Blood samples were collected at 1,2,3and 4 weeks post infection to measure Interleukin 1(IL1),Tummer necrosis factor (TNF),Interferon gamma( IFG) used ELISA, also IgG was measure ELISA test at 2,3and 4 weeks after infection . The results of Serological test showed the infected groups with MG revealed significant increase in the levels of IL-1, IFG, TNF (pro inflammatory cytokines) and IgG production compared with control group ,the group 4( I.T) had higher level of these pro-inflammatory cytokines and Immunoglobulins more than other infected groups in all period post infection. From these result, it was concluded that the local isolate of Mycoplasma gallisepticum has the ability to in induce inflammatory reaction in infected broiler chicken.